ANALISIS PERKEMBANGAN ANIMASI INDONESIA DALAM KONTELS ANIMASI DUNIA - Asti Haningtyas, S.I.Kom, M.I.Kom, Asti Haningtyas, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
The purpose of this study is to evaluate the development of animation in Indonesia based on historical studies to map Indonesian history in the context of world/global animation history at the same time. This study also examines the relationship between the history of Indonesian animation and the history of the first films in Indonesia that occurred during the Dutch colonial period. According to Stephen Cavalier, the entire history of animation can be divided into five major periods, starting with the pre-digital era (The Origin of Animation) and ending with the digital era (1986-2010). Based on the research results, Indonesian animation is produced according to the five main animation cycles of the world, even though the country has long been exposed to foreign films and animation (Disney Studio) has entered Indonesia since the beginning of the world. Indonesia only became a country in the 1950s thanks to the vision of Soekarno, the first president. In the history of animation, 1950 marked the beginning of the transition from the Golden Age of Cartoons, controlled by Disney Studios, to the Golden Age of Cartoons needle television (television era).In the study of the history of animation, the 1950s which lasted half a century was the era of modern animation history. Actually, Indonesian animation has a long history, but compared to the history of world animation, the speed of development of Indonesian animation is relatively slow.